1981
DOI: 10.1530/acta.0.0980043
|View full text |Cite
|
Sign up to set email alerts
|

The relationships between surgical histometry, outcome and pre-treatment in Graves' disease

Abstract: Quantitative histometric methods were used to established the relationship between the extent of thyroid lymphocytic infiltration at operation, and outcome exactly 18 months later in 50 surgically-treated Graves' disease patients prepared by carbimazole and triiodothyronine. Periods of pre-operative treatment, surgical technique, histometric analysis and diagnostic criteria were all standardised. Controls (107) were ob-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Two studies addressing the histologic cellular composition and antibody production were considered not clinically relevant and were excluded. 15,16 Eleven studies were included in the qualitative synthesis; 2 were further excluded from the quantitative analysis. One randomized controlled study reported no difference in mean blood loss between the groups but did not have details sufficient for analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies addressing the histologic cellular composition and antibody production were considered not clinically relevant and were excluded. 15,16 Eleven studies were included in the qualitative synthesis; 2 were further excluded from the quantitative analysis. One randomized controlled study reported no difference in mean blood loss between the groups but did not have details sufficient for analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Among full‐text articles assessed for eligibility, the most common reason for exclusion was that the study was not designed to compare the preoperative administration of any iodine‐containing regimen and no premedication. Two studies addressing the histologic cellular composition and antibody production were considered not clinically relevant and were excluded 15,16 . Eleven studies were included in the qualitative synthesis; 2 were further excluded from the quantitative analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The support in the literature for this finding is mixed. Some agree, while others disagree [17][18][19][20][21].…”
Section: Hypothyroidism After Subtotal Thyroidectomy For Graves' Dise...mentioning
confidence: 99%